Public Record Office - Air Ministry, Board of Trade, Exchequer and Audit Department, Treasury and other record groups - Australian Joint Copying Project; National Library of Australia; Library of New South Wales; Great Britain. Public Record Office (Canberra : Australian Joint Copying Project)
The departments of the Foreign Office fall into two categories political and non-political. There were originally two political departments, one for each Under Secretary, again divided geographically. There were numerous administrative changes after 1815, including the abolition of the third Under Secretaryship in 1827 with subsequent rearrangement of the departments. That then superintended by the Government Under Secretary included Austria, France, Portugal, Spain, Italy, Switzerland, Turkey, Egypt and Greece. The Permanent Under Secretary headed a department including Russia, Prussia, Netherlands, Sweden, Denmark, German States, North and South America and Persia.
National Library of Australia holds microfilm master.
Filmed as part of the Australian Joint Copying Project by the National Library of Australia and the Library of New South Wales.
Australian Joint Copying Project handbook. Part 6 : Public Record Office, various.
Public Record Office - Air Ministry, Board of Trade, Exchequer and Audit Department, Treasury and other record groups.
Original held by Public Record Office, London.
Keywords: Australia -- History -- Sources; New Zealand -- History -- Sources